2018
DOI: 10.1186/s13075-018-1631-y
|View full text |Cite
|
Sign up to set email alerts
|

Methods for high-dimensional analysis of cells dissociated from cryopreserved synovial tissue

Abstract: BackgroundDetailed molecular analyses of cells from rheumatoid arthritis (RA) synovium hold promise in identifying cellular phenotypes that drive tissue pathology and joint damage. The Accelerating Medicines Partnership RA/SLE Network aims to deconstruct autoimmune pathology by examining cells within target tissues through multiple high-dimensional assays. Robust standardized protocols need to be developed before cellular phenotypes at a single cell level can be effectively compared across patient samples.Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 41 publications
(40 reference statements)
8
112
0
Order By: Relevance
“…To examine the impact of therapeutically targeting HBEGF + macrophages in RA joints, we directly assayed synovial tissue from RA patients with definitive RA diagnoses ( 40, 41 ) and extensive joint inflammation confirmed by histologic scoring ( 42, 43 ) (Table S1, n=8). Specifically, in an ex vivo tissue assay, synovium was dissociated into cell suspensions ( 44 ) and cultured with FDA-approved RA medications (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the impact of therapeutically targeting HBEGF + macrophages in RA joints, we directly assayed synovial tissue from RA patients with definitive RA diagnoses ( 40, 41 ) and extensive joint inflammation confirmed by histologic scoring ( 42, 43 ) (Table S1, n=8). Specifically, in an ex vivo tissue assay, synovium was dissociated into cell suspensions ( 44 ) and cultured with FDA-approved RA medications (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
“…The multicenter RA/SLE Network of the Accelerating Medicines Partnership (AMP) consortium enrolled individuals meeting the ACR 2010 RA classification according to protocols approved by the institutional review board at each site ( 22, 44 ). Synovial tissues were collected from ultrasound-guided biopsies or joint replacement surgery and viably frozen in Cryostor CS10 cryopreservation media (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Using established cell lines and isolated primary cells, several studies demonstrated that cell cryopreservation does not alter global transcriptional profiles of cells 23,42,43 . In addition, two studies combined cryopreservation of human tissue (ovarian cancers (Guillaumet-Adkins, 2017 #72)) and human synovial tissue 44 ) with subsequent single-cell RNA-seq analysis. We extend these observations to lung tissue and show that cryopreservation of human lung parenchyma and lung tumor pieces is also compatible with downstream processing using the 10x Genomics single-cell profiling platform.…”
Section: Discussionmentioning
confidence: 99%
“…In rheumatoid arthritis (RA), analysis of synovial tissue with single‐cell RNA sequencing and cytometry by time‐of‐flight mass spectrometry have revealed discrete cell subpopulations with transcriptomic and cell surface expression profiles linked to functional activities . These analyses, focused on the synovium and not the peripheral blood, provided new insights regarding key pathogenic cell–cell interactions and underscore the necessity of examining cellular and molecular events in the target tissue.…”
Section: Characteristics Of Tissue‐resident Memory T Cellsmentioning
confidence: 99%